Digitalization and Product Development of Micro, Small, and Medium Enterprises (MSMEs) in Tonjong Village as a Means of Empowering the Community Toward Prosperous - Hilma Erfiani Baroroh; Widyasari; Yudi Efendi; Afriani (Journal of Community Practice and Social Welfare, 2023)
Micro, Small, and Medium Enterprises (MSMEs) represent a prioritized program within the framework of the Indonesian government's initiatives, bearing substantial potential to enhance a self-reliant and prosperous Indonesian economy. The village of Tonjong in the Bogor Regency, West Java, exhibits significant potential as a locus for MSME activities. This is evident from the occupational pursuits of the Tonjong village community, ranking third in frequency, engaged as MSME operators. In the era of globalization, marked by the advent of highly sophisticated technologies, a considerable number of MSME practitioners in the Tonjong village remain inadequately acquainted with proficient strategies for digital marketing. Consequently, this circumstance has culminated in diminished sales or revenues for the MSME practitioners producing a diverse array of items such as handicrafts and cassava crackers, among others. This predicament underscores the impetus behind community empowerment efforts, realized through the dissemination of insights pertaining to digital product marketing and innovative diversification of cassava cracker flavours within the Tonjong village. The overarching objective centers on amplifying market appeal and garnering broader public interest in these products. The execution of this exposition is meticulously orchestrated to maximize its allure, facilitating the populace's seamless assimilation of diverse knowledge. The didactic approach extends beyond didactic lectures to encompass practical engagements, exemplified by the direct involvement with a digital product marketing application and the multifaceted cassava cracker production process incorporating an array of flavour innovations. The ramifications of this exposition-induced community empowerment yield multifarious outcomes. Notable among these are (1) on the social front, heightened community collaboration for collective advancement; (2) on the economic axis, the community exhibits elevated determination to ameliorate the socio-economic landscape toward public welfare; (3) concerning the educational facet, the community gains fresh insights into the digitalization product of MSME products and acquires novel knowledge regarding innovative cassava cracker flavour profiles.